(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Macasambat RLP, Tan RJ, Margate RE. 2023. Application of hormones and mechanical treatment on breaking the dormancy of G0 “Granola” (Solanum tuberosum) minitubers in Northern Mindanao, Philippines. Asian J Agric 7: 8-14. The study was conducted to identify the best treatment combination for dormancy breaking and sprouting quality for “Granola” minitubers. A comparison was made by wounding and dipping the one-week-old minitubers in different levels of GA3 and BAP (0, 50, and 100 mg/L). Results showed that either 50 or 100 mg/L of GA3 solely influenced the average number of sprouts in minitubers while wounding minitubers highly influenced tuber weight loss by increasing the percent loss in minitubers. In combination with factors such as wounding and 50 mg/L of GA3, it positively influenced the average sprout length, fresh mass of sprouts, and dry mass of sprouts. While the dormancy period and days to dormancy break time (50% minitubers achieved > 2 mm sprout length) were reduced for more than 45 and 50 days, respectively, when factors were combined, such as wounding the minitubers and dipping in the treatment solution having 50 mg/L GA3 and 50 mg/L BAP. The levels of GA3 and BAP (50 and 100 mg/L) showed no significant differences in achieving early dormancy breaking and high sprouting quality in G0 minitubers. Overall, for most of the results in this study, wounding combined with the application of 50 mg/L GA3 was commendable for dormancy breaking and attaining high sprouting quality of “Granola” minitubers.